Light modulates metabolic pathways and other novel physiological traits in the human pathogen Acinetobacter baumannii - Müller, Gabriela Leticia (2017)
Light sensing in chemotrophic bacteria has been relatively recently ascertained. In the human pathogen Acinetobacter baumannii, light modulates motility, biofilm formation, and virulence through the blue-light-sensing-using flavin (BLUF) photoreceptor BlsA. In addition, light can induce a reduction in susceptibility to certain antibiotics, such as minocycline and tigecycline, in a photoreceptorindependent manner. In this work, we identified new traits whose expression levels are modulated by light in this pathogen, which comprise not only important determinants related to pathogenicity and antibiotic resistance but also metabolic pathways, which represents a novel concept for chemotrophic bacteria. Indeed, the phenylacetic acid catabolic pathway and trehalose biosynthesis were modulated by light, responses that completely depend on BlsA. We further show that tolerance to some antibiotics and modulation of antioxidant enzyme levels are also influenced by light, likely contributing to bacterial persistence in adverse environments. Also, we present evidence indicating that surfactant production is modulated by light. Finally, the expression of whole pathways and gene clusters, such as genes involved in lipid metabolism and genes encoding components of the type VI secretion system, as well as efflux pumps related to antibiotic resistance, was differentially induced by light. Overall, our results indicate that light modulates global features of the A. baumannii lifestyle.